Análisis de la prescripción de los impuestos del Gobierno Autónomo Descentralizado del cantón Chone periodo 2012-2015 - Villalba Delgado, Jenny Yuliana (2021)
The Decentralized Autonomous Governments enjoy certain competences granted by the Constitution, among which emphasis is placed on financial autonomy and through this they can create, modify or eliminate taxes that allow them to contribute to the plans or projects proposed within their territory. The purpose of this research is to analyze the tax prescription of the Decentralized Autonomous Government in Chone canton for the period 2012-2015 to propose improvements in the administrative management of collections. For this, study methods such as inductive, deductive and analytical-synthetic were applied, as well as the use of research techniques such as interview and observation with which it was possible to reveal the existing prescription values in the periods studied, since the collection management process was executed, based on these results, it was possible to establish strategies that allow contracting the overdue portfolio and the prescription of taxes. The results obtained, as well as the conclusions that could be reached, show that the year with the highest prescription value was 2013, in addition to the fact that the sum of the four years may represent improvements for the canton. Therefore, it is recommended that efficient collection processes be evaluated, identifying those that are obsolete and do not achieve the collection of taxes owed to the GAD in Chone and in this way an improvement in the collection of these items is achieved.